PUBLIC-PRIVATE PARTNERSHIPS IN FUNCTION OF RAPID ECONOMIC DEVELOPMENT - Ljubiša Vladušić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2012)
This paper contains a review of themost important characteristics of public-privatepartnerships, explaining mutual adjustment ofpublic and private sectors goals during theimplementation of a particular public project. Inaddition, this paper outlines the benefits of publicprivatepartnership through redefining governmentrole in economy ensuring the necessary efficiencyand productivity in the management of publicgoods. The author specially noted that forsuccessful development of public-privatepartnership it is necessary for all stakeholders to beadequately involved in the process and to clearlyrecognize the possibility of better and higherquality in realization of their own interests bydefining the contractual assumptions of riskdiversification. The author also points out that inexplaining the concept of public-privatepartnership it is necessary to distinguish betweenthis kind of contractual relationship and thetraditional ways of providing public services,privatization and concessions. The circumstancessuggest that the experience in strategic merger ofpublic and private sectors in developed countries ispositive and that these processes in countries intransition are delayed both in view of legal aspectand application in practice. The author believesthat not only the legal solutions but also newprocedures and regulations as well as mechanismsfor effective implementation of models of publicprivatepartnership will be of great importance forfurther economic development of the countries intransition.